2020
DOI: 10.1016/j.radcr.2020.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Large vessel vasculitis and the rising role of FDG PET-CT: A case report and review of literature

Abstract: Giant cell arteritis (GCA) is a rare form of large and medium vessel vasculitis affecting about 20 cases per 100,000 persons older than the age of 50 years. GCA results in inflammation and constriction of the temporal arteries, cranial arteries, the aorta, and its major branches. Patients often present with vague constitutional symptoms and fever of unknown origin. GCA is a medical emergency requiring prompt diagnosis and early treatment with glucocorticoids which is essential to avoid irreversible end organ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…An aberrant immune response and immune-mediated pathogenesis are possible explanations for myelitis in COVID-19 patients. MRI is the most frequently used imaging modality for the diagnosis of suspected cases of acute myelitis since it does not only indicate spinal cord lesions but also excludes other possible pathologies that may present with similar clinical symptoms [ 109 ]. Neurologic improvement can be achieved through immunomodulatory treatment such as steroids and plasmapheresis [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…An aberrant immune response and immune-mediated pathogenesis are possible explanations for myelitis in COVID-19 patients. MRI is the most frequently used imaging modality for the diagnosis of suspected cases of acute myelitis since it does not only indicate spinal cord lesions but also excludes other possible pathologies that may present with similar clinical symptoms [ 109 ]. Neurologic improvement can be achieved through immunomodulatory treatment such as steroids and plasmapheresis [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…If high-quality imaging is accessible, the European League Against Rheumatism prefers that high-quality imaging be performed early in the course of suspected GCA over temporal artery biopsy because of reduced morbidity, increased specificity, prompter results, and decreased rates of false-negative results. 2 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…Giant cell arteritis (GCA) is a large- and medium-vessel granulomatous vasculitis that affects the aorta and its major branches, particularly the extracranial branches of the carotid artery. 1 , 2 , 3 GCA occurs primarily in those over 50 years of age and classically manifests as fevers, malaise, headaches, a temporal artery abnormality, jaw claudication, and visual disturbance. 1 The American College of Rheumatology criteria for the diagnosis of GCA require at least 3 of the following: age >50 years, new-onset headaches, temporal artery tenderness, an erythrocyte sedimentation rate of ≥50 mm/hour, and an arterial biopsy demonstrating vasculitis with a mononuclear cell infiltrate or granulomatous inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Many different opinions have arisen as to this phenomenon. Some specialists have attributed it to vascular remodeling, fibrosis, and new angiogenesis [80,81]. In the current research, some experts also considered that subclinical inflammation causes continuous uptake [8].…”
Section: Monitoring Diseasementioning
confidence: 84%
“…Many studies revealed that PET/CT could reliably detect the earliest vascular changes after immunotherapy [72,80].…”
Section: Monitoring Diseasementioning
confidence: 99%